Dosing Regimen of Aditoprim and Sulfamethoxazole Combination for the Glaesserella parasuis Containing Resistance and Virulence Genes - Anxiong Huang; Xiao Huang; Zhihao Zhang; Zonghui Yuan; Lingli Huang; Yulian Wang; Yanfei Tao; Dongmei Chen; Zhenli Liu; Haihong Hao (MDPI AG, 2022)
Glaesserella parasuis (G. parasuis) causes Glasser's disease in pigs and causes high mortality in piglets. The new drug Aditoprim (ADP) alone or combined with Sulfamethoxazole (SMZ) is one of the good choices for treating respiratory infections. The objective of this study was to recommend the optimal dosing regimen for the treatment of G. parasuis infection which contains resistance and virulence genes by ADP/SMZ compound through pharmacokinetics-pharmacodynamics (PK-PD) modeling. The whole genome of the virulent strain G. parasuis H78 was obtained and annotated by whole genome sequencing. The results show that G. parasuis H78 consists of a unilateral circular chromosome with prophages in the genome. The annotation results of G. parasuis H78 showed that the genome contained a large number of virulence-related genes and drug resistance-related genes. The in vitro PD study showed that the antibacterial effect of ADP/SMZ compound against G. parasuis was time-dependent, and AUC/MIC was selected as the PK-PD modeling parameter. The PK study showed that the content of ADP/SMZ compound in pulmonary epithelial lining fluid (PELF) was higher than plasma, and there were no significant differences in ADP and SMZ PK parameters between the healthy and infected group. The dose equation to calculate the optimal dosing regimen of ADP/SMZ compound administration for control of G. parasuis infection was 5/25 mg/kg b.w., intramuscular injection once a day for 3~5 consecutive days. The results of this study provide novel therapeutic options for the treatment of G. parasuis infection to decrease the prevalence and disease burden caused by G. parasuis.